In silico Analysis of Functional Single Nucleotide Polymorphisms in Genes Related to Adipose Tissue Impairment - Abilash, V. G. (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: Adipose tissue is an endocrine organ which is made up of special connective tissue. The major task of this tissue is to accumulate the energy in the form of triacylglycerol (TAG). Adipogenesis is the process of formation of the preadipocyte into the mature adipocyte. Normally adipose tissue is of two types, namely, white adipose tissue (WAT) and brown adipose tissue (BAT). An important role WAT is to store TAG and the significant responsibility BAT is production of heat (thermogenesis). Fat accumulation is identified by the balance between the fat synthesis such as adipogenesis and the fat break down such as lipolysis. When there is excessive amount of intake of food, elevated plasma carbohydrate and triglyceride are involved in lipogenesis in adipose tissue. During fasting condition, there is a process called lipolysis which releases fatty acids and glycerol into the circulation. Our aim is to investigate the single nucleotide polymorphisms (SNP) analysis of genes participated in maintenance of adipose tissue such as hormone sensitive lipase monoglyceride lipase and adiponectin. Materials and Methods: In silico analysis using sorting intolerant from tolerant (SIFT), polyphen 2 was performed for the genes concerned in maintaining adipose tissue homeostasis. Results: SNPs were analyzed for all the genes. Benign and damaging SNPs were identified using SIFT and polyphen 2. Conclusion: As SNPs show suppressed stability, damaging and benign character, they can be further utilized for in vivo studies to determine the role of these genes in adipose tissue homeostasis.